Presence of six different lesion types suggests diverse mechanisms of tissue injury in neuromyelitis optica - Misu, Tatsuro; Höftberger, Romana; Fujihara, Kazuo; Wimmer, Isabella; Takai, Yoshiki; Nishiyama, Shuhei; Nakashima, Ichiro; Konno, Hidehiko; Bradl, Monika; Garzuly, Ferenc; Itoyama, Yasuto; Aoki, Masashi; et al. (Acta neuropathologica, 2013)
Neuromyelitis optica (NMO) is an autoimmune disease targeting aquaporin 4 (AQP4), localized mainly at the astrocytic foot processes. Loss of AQP4 and glial fibrillary acidic protein (GFAP) was reported, but the pathological significance of astrocytopathy is still controversial. Here we show that active lesions in NMO display a wide spectrum of pathology even within a single tissue block of an individual patient. We have distinguished six different lesion types. The first reflects complement deposition at the surface of astrocytes, associated with granulocyte infiltration and astrocyte necrosis and followed by demyelination, global tissue destruction and the formation of cystic, necrotic lesions (lesion type 2). Such destructive lesions lead to Wallerian degeneration in lesion-related tracts (lesion type 3). Around active NMO lesions AQP4 may selectively be lost in the absence of aquaporin 1 (AQP1) loss or other structural damage (lesion type 4). Another pattern is characterized by clasmatodendrosis of astrocytes, defined by cytoplasmic swelling and vacuolation, beading and dissolution of their processes and nuclear alterations resembling apoptosis, which was associated with internalization of AQP4 and AQP1 and astrocyte apoptosis in the absence of complement activation. Such lesions give rise to extensive astrocyte loss, which may occur in part in the absence of any other tissue injury, such as demyelination or axonal degeneration (lesion type 5). Finally, lesions with a variable degree of astrocyte clasmatodendrosis are found, which show plaque-like primary demyelination that is associated with oligodendrocyte apoptosis, but with preservation of axons (lesion type 6). In active multiple sclerosis (MS) lesions astrocytes reveal changes of reactive protoplasmatic or fibrillary gliosis. Only in a subset of lesions, in patients with aggressive disease, loss of AQP4 is observed in the initial stage of their formation, which is associated with retraction of astrocyte processes in the absence of complement deposition, granulocyte infiltration or loss of AQP1 or astrocytes. Our data underline the primary assault of astrocytes in NMO lesions, but also indicate that different mechanisms of tissue injury operate in parallel in the same patient and even within the same lesion.